Prevalensi Trikomoniasis pada Wanita Risiko Tinggi di Kawasan Wisata Baturraden Kabupaten Banyumas - Sri Widyastuti; Adhi Kumoro Setya (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Trichomoniasis is a sexually transmitted disease with a high incidence. People with multiple sexual partners are believed to be the main transmission factors. In recent years, the number of sexually transmitted infections in Banyumas has been quite high. The existence of Gang Sadar which is the residence of women sex workers, with a strategic location and close to tourist attractions in Baturraden, makes many people visit. These conditions increase the risk of transmission of trichomoniasis in the region. The purpose of this study was to find out the number of cases of trichomoniasis on urine samples of high-risk women in the Baturraden tourist area. This research descriptive in nature by involving female research respondents with high risk job. In each research respondent an examination was carried out from the urine specimen and as a support for the collection of respondent's life background. The data is presented in tables and calculated percentage of infected respondentsTrichomonas vaginalis. From the inspection results laboratory found parasitesTrichomonas vaginalis as many as 2 people from30 research respondents. Based on sociodemographic data, case finding occurredon respondents with characteristics; over 21 years old, last education Middle and high school, karaoke guide profession and prostitutes and marital status have not married and divorced. From the data on the sexual activity of the respondents, came up with characteristics; all showed symptoms of abnormal vaginal discharge and odor as wellserving 1-3 customers per day. The results of this study obtained conclusions that trichomoniasis cases were 6.7% with heterogeneous characteristics of respondents.